2013
DOI: 10.5551/jat.15420
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Ankle Vascular Index in Subjects with Dyslipidaemia and Other Cardiovascular Risk Factors

Abstract: Aim:The cardio-ankle vascular index (CAVI) is a novel non-invasive marker of arterial stiffness and atherosclerosis. The aim of this work was to examine whether the CAVI value in patients with dyslipidaemia (DLP) is increased by the presence of other cardiovascular risk factors: hypertension, diabetes mellitus, and smoking. Methods: A total of 392 subjects with DLP (166 male, 226 female), with a median age of 58.5 and 5-95 percentile range 32.2-73.9 years were examined. CAVI was measured using the VaSera 1500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Takaki et al reported that the CAVI has a poor relationship with both the total and LDL cholesterol levels, and there is no observed correlation between the CAVI values and triglyceride and HDL cholesterol levels (9). Satoh et al reported that an increased CAVI is significantly correlated with the triglycerides and HDL cholesterol levels in men, but not women (46). This observation may reflect a difference in the pathophysiological mechanisms underlying dyslipidemia between men and women.…”
Section: Discussionmentioning
confidence: 87%
“…Takaki et al reported that the CAVI has a poor relationship with both the total and LDL cholesterol levels, and there is no observed correlation between the CAVI values and triglyceride and HDL cholesterol levels (9). Satoh et al reported that an increased CAVI is significantly correlated with the triglycerides and HDL cholesterol levels in men, but not women (46). This observation may reflect a difference in the pathophysiological mechanisms underlying dyslipidemia between men and women.…”
Section: Discussionmentioning
confidence: 87%
“…In our study population, however, no blood lipid parameters were associated with the ageadjusted CAVI ( Table 2). In concordance with these results, several studies have failed to detect a significant association between the CAVI and blood lipid levels [36][37][38] . Higashiyama et al 36) reported that the CAVI is more strongly correlated with the high-sensitivity C-reactive protein (hs-CRP) level than with the LDL cholesterol level.…”
Section: Resultsmentioning
confidence: 52%
“…Specifically, studies that compared CAVI with invasive coronary artery angiography or cardiac computed tomography angiography (CCTA) indicated a significant relationship between CAVI and coronary artery disease (CAD) . Although CAVI has been extensively studied and recognized as a tool to predict cardiovascular risk, most studies have been conducted in Asian countries . This is a pilot study to investigate whether CAVI can predict severity, extent, and burden of CAD by comparing results with CCTA in a US population.…”
Section: Introductionmentioning
confidence: 99%